2007
DOI: 10.1016/j.abb.2006.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of superoxide production from aldehyde oxidase: An important source of oxidants in biological tissues

Abstract: Aldehyde oxidase, a molybdoflavoenzyme that plays an important role in aldehyde biotransformation, requires oxygen as substrate and produces reduced oxygen species. However, little information is available regarding its importance in cellular redox stress. Therefore, studies were undertaken to characterize its superoxide and hydrogen peroxide production. Aldehyde oxidase was purified to >98% purity and exhibited a single band at ∼290 kDa on native polyacrylamide gradient gel electrophoresis. Superoxide generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 58 publications
(67 reference statements)
4
60
0
Order By: Relevance
“…The three bands were analyzed by matrix-assisted laser desorption ionization peptide mapping and identified to be the degradation products of hAOX1. Similar bands also were observed in purified mAOX3 (Mahro et al, 2011) and AOX1 protein preparations of mouse and rat origin (Kundu et al, 2007;Schumann et al, 2009). These products were never detectable upon native PAGE (Kundu et al, 2007;Mahro et al, 2011) and fast protein liquid chromatography.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The three bands were analyzed by matrix-assisted laser desorption ionization peptide mapping and identified to be the degradation products of hAOX1. Similar bands also were observed in purified mAOX3 (Mahro et al, 2011) and AOX1 protein preparations of mouse and rat origin (Kundu et al, 2007;Schumann et al, 2009). These products were never detectable upon native PAGE (Kundu et al, 2007;Mahro et al, 2011) and fast protein liquid chromatography.…”
Section: Resultssupporting
confidence: 58%
“…Similar bands also were observed in purified mAOX3 (Mahro et al, 2011) and AOX1 protein preparations of mouse and rat origin (Kundu et al, 2007;Schumann et al, 2009). These products were never detectable upon native PAGE (Kundu et al, 2007;Mahro et al, 2011) and fast protein liquid chromatography. All of this suggested that the observed degradation products are generated by the reductive conditions intrinsic to SDS-PAGE.…”
Section: Resultssupporting
confidence: 58%
“…However, under disease conditions or with alcohol ingestion, these levels are further elevated. We have previously measured that the tissue levels of AO are ϳ60 g/g tissue in liver, 35 g/g in lung, and 5.1 g/g in heart with the activity corresponding to 1.8 units/mg enzyme (21,35). In the presence of physiological levels of NADH (100 M) or aldehyde (50 M), the rate of NO generation followed typical Michaelis-Menten kinetics (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DMAC oxidations and absorbance changes were converted to units of enzyme activity (IU) using an extinction coefficient ⑀ ϭ 30.5 mM Ϫ1 cm Ϫ1 . One unit of enzyme activity was defined as the amount of enzyme required to oxidize 1 mol of DMAC/min at 30°C (35). The activity of freshly isolated AO was ϳ1.8 units/mg but declined over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation